Desenlaces materno perinatales de gestantes adolescentes en un hospital de Lima del 2017 al 2020 - Urbina-Alvarez, Claudia (2024)
Pregnancy is a risk factor for some obstetric complications among adolescents, especially in early adolescence. Objective: The general objective was to describe the demographic, clinical and perinatal characteristics of pregnant adolescents and their newborns in a hospital in Lima between 2017 and 2020.   Materials and methods: Cross-sectional descriptive observational study of pregnant adolescents treated at the Edgardo Rebagliati Martins Hospital between 2017 and 2020.   A census sample was taken that included all the pregnant women registered in the database.   Data of the services and of those that meet inclusion and not exclusion criteria.   Statistical records were transferred to Excel spreadsheets for coding and could be imported into STATA version 12.0 for Windows for further analysis.   Results: Among the maternal complications, premature rupture of membranes was more common in young adults; among young newborns, the most common complication was neonatal respiratory distress syndrome (18 cases).   Conclusions: It was concluded that adolescent pregnancy increases morbidity and perinatal morbidity, which is also a sociocultural problem.